Kewarganegaraan dalam Hukum Internasional : Implikasi dari Perjanjian Ekstradisi dan Imunitas Diplomatif - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Muhammad Nur Sokhib; Septian Dwi Kurniawati; Fina Thazha Eka Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research discusses the relationship between citizenship in international law, with a focus on two implications, namely extradition treaties and diplomatic immunity. Citizenship has an important role in the extradition process and the application of diplomatic immunity because often an individual's citizenship status influences legal and diplomatic decisions. Through literature analysis, recent case studies, and international comparisons, this research identifies that legal and political decisions on extradition and the application of diplomatic immunity are influenced by citizenship. Modern cases, such as the involvement of Julian Assange and Chelsea Manning, forgivemin prove the lack of balancing between international obligations and individual rights. Variations in legal practices between countries, including differences between European countries, the United States, and Asian countries, highlight the need for more consistent international standards. This research recommends increased multilateral dialogue, transparency of legal processes, and long-term case studies to improve understanding and practice regarding citizenship in international law.